Problem-based Learning: Questioning or Problems in Social Science (in Thai) - Somboonboorana, Siriporn (Asia Social Issues, 2013)
Problem - based Learning (PBL) is a learning method that is derived from the concept of Constructivism. It creates a new knowledge of the problems in the real world taken as the context for learning to help the students achieve skills in critical thinking and problem solving. It is a new teaching technique and method that encourage students to take action on their own. Starting with the problem is to encourage the students to use different methods of acquiring knowledge from diverse sources of knowledge for problem solving. The students were not prepared to deal with those problems before the lessons. When applied to the teaching of “Social Sciences” that focuses on techniques such as questioning interpreting and analysis, Problem - based Learning leads to various directions of understanding the phenomenon. The weakness thus is in the step of “Problem Definition”. The ability in trending imagination in Social Sciences and interpretation and analysis of the problems of the real world has to be strengthened. The problem that is need as a trigger needs to be carefully selected emphasized. This article focuses on the importance of using Problem - based Learning in the study of social reality. The result of which will be the understanding of the problem or the problem of Social Sciences to explain the reality of the phenomenon actually happening in society. PBL: โจทย์ปัญหาหรือสร้างปัญหาทางสังคมศาสตร์ การเรียนการสอนแบบใช้ปัญหาเป็นฐาน (Problem - based Learning : PBL) ถือว่าเป็นรูปแบบการเรียนรู้หนึ่งที่เกิดขึ้นจากแนวคิดการ เรียนรู้แบบการสร้างความรู้ใหม่โดยผู้เรียน นับว่า เป็นการสร้างความรู้ใหม่จากการใช้ปัญหาที่เกิด ขึ้นในโลกแห่งความจริง (Real World) เป็นบริบท การเรียนรู้ เพื่อให้ผู้เรียนเกิดทักษะในการคิด วิเคราะห์และคิดแก้ปัญหา อีกทั้งเป็นเทคนิคการ สอนแบบใหม่และวิธีวิทยาที่ส่งเสริมให้ผู้เรียน ได้ลงมือปฏิบัติด้วยตนเอง หรือวิธีการเรียนรู้ที่ เริ่มต้นด้วยการใช้ปัญหาเป็นตัวกระตุ้นให้ผู้เรียน ไปศึกษาค้นคว้าแสวงหาความรู้ด้วยวิธีการต่าง ๆ จากแหล่งวิทยาการที่หลากหลาย เพื่อนำมาใช้ใน การแก้ปัญหา โดยที่มิได้มีกาศึกษาหรือเตรียม ตัวล่วงหน้าเกี่ยวกับปัญหาดังกล่าวมาก่อน เมื่อนามาใช้กับการเรียนการสอนในรายวิชาทางด้าน “สังคมศาสตร์” ที่ให้ ความสาคัญกับการตั้งคาถาม การตีความ การวิเคราะห์ เป็นต้น น่า จะเป็นไปในทิศทางเดียวกันได้ แต่ก็ปรากฏว่าต้องพบกับจุดอ่อนของ การ “ตั้งโจทย์ปัญหา” กับขีดความสามารถที่ปลดล็อกการจินตนาการ ทางสังคมศาสตร์ กับการตีความและวิเคราะห์ปรากฏการณ์ทางสังคม และความจริงที่เกิดขึ้นในสังคม ดังนั้นจึงทำให้ต้องหันกลับมาให้ความ สำคัญและพิจารณากับ “โจทย์ปัญหา” ของการใช้ปัญหาเป็นฐานให้ มากขึ้นและชัดเจนขึ้น บทความนี้ต้องการนาเสนอความสำคัญของการเรียนการสอนแบบใช้ปัญหาเป็นฐานกับการศึกษาความเป็นจริง ทางสังคม อันส่งผลต่อการทำความเข้าใจในโจทย์หรือปัญหาของวิชา ทางด้านสังคมศาสตร์ที่ต้องอธิบายความเป็นจริงของปรากฏการณ์จริงที่เกิดขึ้นในสังคม